P(-2.81>z>1.05)=
P(−2.81<z<1.05)=P(z<1.05)−P(z<−2.81)P(-2.81<z<1.05)=P(z<1.05)-P(z<-2.81)P(−2.81<z<1.05)=P(z<1.05)−P(z<−2.81)
From Standard Normal Distribution Table,
P(z < 1.05) = 0.85314
P(z < -2.81) = 0.00248
⟹ P(z<1.05)−P(z<−2.81)=0.85314−0.00248=0.85066\implies P(z<1.05)-P(z<-2.81)= 0.85314-0.00248 = 0.85066⟹P(z<1.05)−P(z<−2.81)=0.85314−0.00248=0.85066
Hence, P(−2.81>z>1.05)=0.85066\boxed{P(-2.81>z>1.05)=0.85066}P(−2.81>z>1.05)=0.85066
Need a fast expert's response?
and get a quick answer at the best price
for any assignment or question with DETAILED EXPLANATIONS!
Comments
Leave a comment